Inside the White Box: Unpacking the Determinants of Quality and Vertical Specialization - Esteban Jaimovich; Boryana Madzharova; Vincenzo Merella (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper explores patterns of quality differentiation and specialization relying on model-level panel data of retail sales and prices of refrigerators across 23 countries in the European Union. Unlike customs data aggregated at the product category, typically used in the literature, model-level data allow us to test for the presence of nonhomotheticities by comparing market shares of identical models across different markets. We measure quality at the model level, account for varying willingness-to-pay for quality at different levels of income, and link quality measures to objective model attributes. Using originally assembled data on the country of manufacture of each model, we study patterns of quality specialization by brands with plants in multiple countries. We find that firms locate the production of their higher-quality models in richer countries, and argue that such patterns of quality specialization are driven mainly by a home-market effect linked to nonhomothetic preferences.
Keywords: F10; F14; 330; inferred quality; nonhomothetic CES; home-market effect; quality specialization